2020
DOI: 10.7717/peerj.9130
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of TCP family genes in Brassica juncea var. tumida

Abstract: Background Teosinte branched1/Cycloidea/proliferating cell factors (TCPs) are plant-specific transcription factors widely involved in leaf development, flowering, shoot branching, the circadian rhythm, hormone signaling, and stress responses. However, the TCP function in Brassica juncea var. tumida, the tumorous stem mustard, has not yet been reported. This study identified and characterized the entire TCP family members in B. juncea var. tumida. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 91 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Owing to the development, duplications, and divergence of TCP genes, the gymnosperms and angiosperms plants possess bigger TCP gene families containing more than ten TCP members ( Martín-Trillo and Cubas, 2010 ). Over the past few years, TCP gene families have been reported in various crop plants such as Arabidopsis thaliana ( Yao et al, 2007 ), Moso bamboo ( Liu et al, 2018 ), sweet potato ( Ren et al, 2021 ), cucumber ( Wen et al, 2020 ), rice ( Yao et al, 2007 ), Brassica rapa ( Du et al, 2017 ); Brassica juncea ( He et al, 2020 ); and cotton ( Ma et al, 2014 ; Yin et al, 2018 ), etc. To our best knowledge, the TCP gene family has not been fully characterized in the rapeseed genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the development, duplications, and divergence of TCP genes, the gymnosperms and angiosperms plants possess bigger TCP gene families containing more than ten TCP members ( Martín-Trillo and Cubas, 2010 ). Over the past few years, TCP gene families have been reported in various crop plants such as Arabidopsis thaliana ( Yao et al, 2007 ), Moso bamboo ( Liu et al, 2018 ), sweet potato ( Ren et al, 2021 ), cucumber ( Wen et al, 2020 ), rice ( Yao et al, 2007 ), Brassica rapa ( Du et al, 2017 ); Brassica juncea ( He et al, 2020 ); and cotton ( Ma et al, 2014 ; Yin et al, 2018 ), etc. To our best knowledge, the TCP gene family has not been fully characterized in the rapeseed genome.…”
Section: Discussionmentioning
confidence: 99%
“…rapa) ( Du et al, 2017 ); 63 TCP members in Brassica juncea var. tumida ( He et al, 2020 ), 73 TCP members in allotetraploid cotton ( Gossypium hirsutum L.) ( Yin et al, 2018 ), etc. Several studies have shown that TCP genes play significant roles in plant growth and developmental processes, including trichome formation ( Wang et al, 2013 ), seed germination ( Zhang et al, 2019 ), petal development ( van Es et al, 2018 ), floral development ( Li et al, 2019 ), shoot branching ( Braun et al, 2012 ), and leaf anatomical morphology ( Ren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The formation and development of bulblet is a complex process regulated by a series of transcription factors (Gao et al 2018 ; Moreno-Pachon et al 2016 ). The teosinte branched1/cycloidea/proliferating cell factor1 (TCP) is a special transcription factor family involved in activation or inhibition cell proliferation and related to branching, leaf development, and germination (He et al 2020 ). TCP transcription factors have been reported in many plant species, such as 24 TCP in Arabidopsis (Li 2015 ), 39 TCP in Brassica rapa L .…”
Section: Discussionmentioning
confidence: 99%
“…During the tuber swollen stage of Brassica juncea var. tumida, the expression of 6 BjTCP genes were significantly upregulated (He et al 2020 ). The root hair, density, and stem trichome were increased when the GbTCP5 gene in transgenic Arabidopsis was overexpressed (Wang et al 2020b ).…”
Section: Discussionmentioning
confidence: 99%
“…juncea var. tumida has a larger genome, which is an allotetraploid (AABB), resulting from the hybridization between diploid ancestors of B. rapa (AA) and B. nigra (BB), followed by spontaneous chromosome doubling ( He et al, 2020 ). Therefore, the number of NAC genes in B .…”
Section: Discussionmentioning
confidence: 99%